Peran Guru Pendidikan Agama Islam Dalam Mengembangkan Pendidikan Multikultural - Huda, Mualimul (Sekolah Tinggi Agama Islam Ma`arif Kalirejo Lampung Tengah, 2022)
The crisis that has penetrated Indonesia now is a multidimensional crisis, starting from a crisis of morality, ethics and tolerance. The decline in moral values ​​in students has now become a challenge and warning for all parties, especially educational institutions, the role of teachers and parents. Many cases happen to young people, ranging from cases of intolerance, bullying, promiscuity and other deviant acts. Various multidimensional crises in Indonesia, whether recognized or not are part of the cultural problems one of the causes is the diversity of cultures that exist in our society. Cultural diversity should not be a cause of discrimination, injustice, suspicion and various human rights violations, but rather a force to build togetherness. The teacher has an important role in the transmission of science, information, character education, research, recreation, and cultural understanding. The thought of multicultural Islamic education in Indonesia is based on Islamic teachings as a source of thought. Multiculturality is a sunnatullah that can not be avoided in it contains important values ​​for the development of faith and social life the role of the teacher plays an important role in rectifying the understanding of Islam that deviates from the understanding of Islam which is